Persepsi Perawat tentang Restrain Pada Pasien Perilaku Kekerasan di Klinik Jiwa - Tantan Hadiansyah; Asep Edyana; A. Nur Anna AS; Rifki Sakinah Nompo; Laeli Farkhah; Andria Pragholapati (Universitas Malahayati Lampung, 2024)
ABSTRACT Psychiatric emergencies are often accompanied by violent behavior that requires immediate intervention. Nurses in psychiatric clinics frequently encounter patients exhibiting violent behavior, and restraint is one of the methods used. This study aims to understand nurses' perceptions of restraint on patients with violent behavior. The study aims to explore nurses' perceptions regarding the use of restraint on patients with violent behavior in psychiatric clinics and the factors influencing nurses' readiness and confidence in such situations. A qualitative descriptive approach with total sampling was used. Data were collected through in-depth interviews and participant observations of seven nurses at the Psychiatric Clinic. Data analysis was conducted using thematic analysis methods, including transcription, coding, categorization, identification of main themes, and data validation. Most nurses feel less confident in handling patients with violent behavior without restraint training. Longer work experience increases confidence but does not replace the need for formal training. Educational background influences nurses' theoretical knowledge but does not fully guarantee practical readiness in applying restraint. Restraint training is highly necessary to improve nurses' readiness and confidence in handling violent patients. Nurses with higher educational backgrounds still require practical training to ensure safe and effective application. Keywords: Nurse Perception, Restraint, Violent Behavior, Psychiatric Clinic ABSTRAK Kedaruratan psikiatri sering disertai perilaku kekerasan yang memerlukan intervensi segera. Perawat di klinik jiwa sering menghadapi pasien yang berperilaku kekerasan, dan restrain adalah salah satu metode yang diterapkan. Penelitian ini bertujuan memahami persepsi perawat terhadap restrain pada pasien dengan perilaku kekerasan. Penelitian ini bertujuan mengeksplorasi persepsi perawat mengenai penggunaan restrain pada pasien dengan perilaku kekerasan di klinik jiwa, serta faktor-faktor yang mempengaruhi kesiapan dan kepercayaan diri perawat dalam situasi tersebut. Pendekatan deskriptif kualitatif dengan total sampling digunakan. Data dikumpulkan melalui wawancara mendalam dan observasi partisipan terhadap tujuh perawat di Klinik Jiwa. Analisis data dilakukan dengan metode analisis tematik yang mencakup transkripsi, pengodean, kategorisasi, identifikasi tema utama, dan validasi data. Sebagian besar perawat merasa kurang percaya diri dalam menangani pasien dengan perilaku kekerasan tanpa pelatihan restrain. Pengalaman kerja yang lebih lama meningkatkan rasa percaya diri, namun tetap tidak menggantikan kebutuhan akan pelatihan formal. Latar belakang pendidikan mempengaruhi pengetahuan teoritis perawat, tetapi tidak sepenuhnya menjamin kesiapan praktis dalam penerapan restrain. Pelatihan restrain sangat diperlukan untuk meningkatkan kesiapan dan kepercayaan diri perawat dalam menangani pasien kekerasan. Perawat dengan latar belakang pendidikan tinggi tetap memerlukan pelatihan praktis untuk penerapan yang aman dan efektif. Kata Kunci: Persepsi Perawat, Restrain, Perilaku Kekerasan, Klinik Jiwa